Introduction [to] Nearly zero energy building refurbishment - Pacheco-Torgal, F. (2013)
This chapter starts with an overview on CO2 emissions and climate change addressing key investigations and important related events. The situation of the European Union concerning energy efficiency is described. A short analysis of the nearly zero-energy building (NZEB) concept is presented. A book outline is also presented.